The Complex Cell Wall Composition of Syncytia Induced by Plant Parasitic Cyst Nematodes Reflects Both Function and Host Plant - Zhang, Li; Lilley, Catherine J.; Imren, Mustafa; Knox, J. Paul; Urwin, Peter E. (Frontiers in Plant Science, 2017)
Plant–parasitic cyst nematodes induce the formation of specialised feeding structures, syncytia, within their host roots. These unique plant organs serve as the sole nutrient resource for development and reproduction throughout the biotrophic interaction. The multinucleate syncytium, which arises through local dissolution of cell walls and protoplast fusion of multiple adjacent cells, has dense cytoplasm containing numerous organelles, surrounded by thickened outer cell walls that must withstand high turgor pressure. However, little is known about how the constituents of the syncytial cell wall and their conformation support its role during nematode parasitism. We used a set of monoclonal antibodies, targeted to a range of plant cell wall components, to reveal the microstructures of syncytial cell walls induced by four of the most economically important cyst nematode species, Globodera pallida, Heterodera glycines, Heterodera avenae and Heterodera filipjevi, in their respective potato, soybean and spring wheat host roots. In situ fluorescence analysis revealed highly similar cell wall composition of syncytia induced by G. pallida and H. glycines. Both consisted of abundant xyloglucan, methyl-esterified homogalacturonan and pectic arabinan. In contrast, the walls of syncytia induced in wheat roots by H. avenae and H. filipjevi contain little xyloglucan but are rich in feruloylated xylan and arabinan residues, with variable levels of mixed-linkage glucan. The overall chemical composition of syncytial cell walls reflected the general features of root cell walls of the different host plants. We relate specific components of syncytial cell walls, such as abundant arabinan, methyl-esterification status of pectic homogalacturonan and feruloylation of xylan, to their potential roles in forming a network to support both the strength and flexibility required for syncytium function.